Rain, rain, rain forest - Guiberson, Brenda Z.; Jenkins, Steve, 1952- (New York : Henry Holt, 2004)
Takes a journey through a rain forest, investigating the plants and animals that dwell there.
3.9
K-3
K-3
Wilson's Children
School Library Journal
Book Links (A.L.A.)
Keywords: Rain forest ecology -- Juvenile literature; Rain forest animals -- Juvenile literature; Rain forest plants -- Juvenile literature; Rain forests; Rain forest ecology; Rain forest animals; Rain forest plants; Ecology; Rain forests; Rain forest ecology; Rain forest animals; Rain forest plants; Ecology; Picture books for children